Rectus femoris muscle elasticity and stiffness correlates with maximal oxygen consumption in triathletes - Gavronski, G.; Reimets, A.; Talts, J.; Koovit, I.; Mandel, T.; Viir, R.; Vasar, E.; Veraksitš, A. (bioRxiv, 2023)
VO2max is considered single best indicator of cardiovascular fitness and aerobic endurance. We analyzed retrospectively, are there any relationships between muscle parameters and oxygen consumption in a study where the myoton equipment was used to establish muscle biomechanical properties, such as elasticity, stiffness, and tension (measured as oscillation frequency) in triathletes. Eight muscles were studied in 14 male triathletes over three years. Relaxed and contracted states of muscles were measured. VO2max was recorded in these athletes up to four times during this period. Average values were calculated for each athlete and High (max 71.8-min 62.3 ml/kg/min) and Low (59.1-51.3) oxygen consumption groups were formed. Higher oxygen consumption correlated significantly (r=-0.58; p=0.029) with improved elasticity (represented by smaller decrement values) of the rectus femoris muscle in a contracted state. Also, in the High VO2max group, this muscle (in a relaxed state) was significantly more elastic and stiffer at the same time compared to the Low group. An ultrasound registration was also conducted to observe the depth of the device's impact in the posterior crural muscles. It was confirmed that deep and substantial tissue disturbances were caused by this impact. According to our findings, myotonometry is an adequate method to establish muscle parameters. Elasticity and stiffness of the rectus femoris muscle may determine success in triathlon.